2020
DOI: 10.1016/j.yexcr.2020.112204
|View full text |Cite
|
Sign up to set email alerts
|

Network perturbation analysis in human bronchial epithelial cells following SARS-CoV2 infection

Abstract: Background SARS-CoV2, the agent responsible for the current pandemic, is also causing respiratory distress syndrome (RDS), hyperinflammation and high mortality. It is critical to dissect the pathogenetic mechanisms in order to reach a targeted therapeutic approach. Methods In the present investigation, we evaluated the effects of SARS-CoV 2 on human bronchial epithelial cells (HBEC). We used RNA-seq datasets available online for identifying SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 57 publications
(61 reference statements)
4
35
0
1
Order By: Relevance
“…Gene DNAH7 encodes dynein axonemal heavy chain 7, which is a component of the inner dynein arm of ciliary axonemes [ 33 ]. A recently published paper showed that gene DNAH7 is the most downregulated gene after infecting human bronchial epithelial cells with SARS-CoV2 [ 34 ]. The authors of that study speculated that the downregulation of gene DNAH7 causes the reduction of function of respiratory cilia.…”
Section: Discussionmentioning
confidence: 99%
“…Gene DNAH7 encodes dynein axonemal heavy chain 7, which is a component of the inner dynein arm of ciliary axonemes [ 33 ]. A recently published paper showed that gene DNAH7 is the most downregulated gene after infecting human bronchial epithelial cells with SARS-CoV2 [ 34 ]. The authors of that study speculated that the downregulation of gene DNAH7 causes the reduction of function of respiratory cilia.…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods do not provide insight into the severity of infection. Computed tomography (CT), lung pathology, and biomarkers have all been suggested to provide concurrent diagnostic and risk stratification assistance [ 8 ]. The application of CT to disease staging is now in worldwide use where it is available; however, chest radiography is a simpler, cheaper, more widely available resource.…”
Section: Introductionmentioning
confidence: 99%
“…The therapy for COVID-19 remains to be established, although non-pharmacological and preventive treatments have been recommended (5). Like other coronaviruses, SARS-CoV-2 is neurotropic (6). Neurological complications of COVID-19 include cerebrovascular disease, meningitis/encephalitis, acute necrotizing hemorrhagic encephalopathy and Guillain-Barré syndrome (7).…”
Section: Introductionmentioning
confidence: 99%